Fabrication of thin films on an anode support with surface modification for high-efficiency intermediate-temperature solid oxide fuel cells via a dip-coating method. (1st November 2016) - Jang, Inyoung; Kim, Chanho; Kim, Sungmin; Yoon, Heesung
Graphical abstract: Abstract: We studied the surface morphology of a modified anode structure that is capable of increasing the triple phase boundary (TPB) and the effect of its morphological feature on the electrochemical performances. The top surface area of the anode functional layer (AFL) was increased to extend the TPB length and the high contact area between the electrolyte and the AFL. To increase the top surface area of the AFL, carbon particles, which have a particle size larger than 10 μm, were mixed with the AFL slurry solution and coated on the anode support layer. Carbon particles were burned-out prior to coating the electrolyte layer on the AFL. As a result, the electrolyte could be successfully coated on the top of the AFL, which has a rough morphology. Enhanced roughness of the top surface of the AFL via the modification process was verified through atomic force microscopy (AFM) analysis. In addition, the microstructures of the contact area between the AFL and electrolyte were studied through the use of scanning electron microscopy (SEM). The Solid Oxide fuel cell (SOFC)with a modified AFL displayed excellent performance in power density and electrochemical impedance spectroscopy (EIS), in comparison with a cell that had a normal AFL. Additionally, the cell with a modified AFL exhibited a 74% higher peak power density value than the cell with a flat AFL and displayed the lowest resistance value in EIS results.